Coffee Consumption and Cancer Risk: An Assessment of the Health Implications Based on Recent Knowledge - Pauwels, Ernest K.J.; Volterrani, Duccio (Medical principles and practice, 2021)
A significant number of studies suggest that coffee consumption reduces cancer risk. This beneficial effect is usually ascribed to the presence of polyphenolic antioxidants and anti-inflammatory agents, including caffeine, cafestol, kahweol, and chlorogenic acids. To summarize recent literature on this subject, we performed a bibliographic search in PubMed and Embase over the period January 2005 to December 2020 to identify cohort studies and meta-analysis (with data collection ensuring quality of selected reports) that could provide quantitative data on the relationship between coffee consumption and common cancers. The totality of eligible scientific articles supports the evidence that coffee intake is inversely associated with risk of hepatocellular cancer and, to a slight extent, risk of breast cancer among postmenopausal women. As to the association with other organs, including the esophagus, pancreas, colorectum, kidneys, bladder, ovaries, and prostate, the results are less clear as reports reveal conflicting results or statistically nonsignificant data. Therefore, this overview does not provide broad-based conclusions. Important uncertainties include general study design, inhomogeneous patient sampling, different statistical analysis (deliberate), misreporting of socioeconomic status, education, coffee-brewing methods, consumption of caffeinated or decaffeinated coffee, smoking habits, and alcohol intake. Clearly, more epidemiologic research needs to be conducted before solid science-based recommendations can be made with regard to coffee consumption.